Introduction of a putative biocontrol agent into a range of phytoplasma‐ and liberibacter‐susceptible crop plants. Issue 4 (11th December 2017) - Lidor, Ofir; Dror, Orit; Hamershlak, Dor; Shoshana, Nofar; Belausov, Eduard; Zahavi, Tirtza; Mozes‐Daube, Netta; Naor, Vered; Zchori‐Fein, Einat; Iasur‐Kruh, Lilach; Bahar, Ofir
Abstract: BACKGROUND: Phytoplasma, the causative agent of Bois Noir disease of grapevines, are vectored by the planthopper Hyalesthes obsoletus (Hemiptera: Cixiidae). A Dyella ‐like bacterium (DLB) isolated from H. obsoletus inhibits the growth of Spiroplasma melliferum, a cultivable relative of phytoplasma. Additional evidence suggests that DLB can reduce the symptoms of yellows disease in grapevine plantlets. The aim of this study was to test whether DLB could colonize a range of phytoplasma‐ and liberibacter‐sensitive crop plants, and thus assess its potential agricultural use. RESULTS: Vitex agnus‐castus, the preferred host plant of H. obsoletus was found to be a natural host of DLB, which was successfully introduced into a range of crop plants belonging to seven families. The most effective DLB application method was foliar spraying. Microscopy observation revealed that DLB aggregated on the leaf surface and around the stomata, suggesting that this is its route of entry. DLB was also present in the vascular tissues of plants, indicating that it moved systemically through the plant. CONCLUSIONS: DLB is a potential biocontrol agent and its broad spectrum of host plants indicates the possibility of its future use against a range of diseases caused by phloem‐limited bacteria. © 2017 Society of Chemical Industry Abstract : Vector‐transmitted bacterial diseases are difficult to control. This study shows that the putative biocontrol agent, Dyella ‐Like Bacterium, can be applied to and persist in multiple crop plants.